Revitalizing the drug pipeline: AntibioticDB, an open access database to aid antibacterial research and development. (11th June 2018) - Farrell, L J; Lo, R; Wanford, J J; Jenkins, A; Maxwell, A; Piddock, L J V
Abstract: The current state of antibiotic discovery, research and development is insufficient to respond to the need for new treatments for drug-resistant bacterial infections. The process has changed over the last decade, with most new agents that are in Phases 1–3, or recently approved, having been discovered in small- and medium-sized enterprises or academia. These agents have then been licensed or sold to large companies for further development with the goal of taking them to market. However, early drug discovery and development, including the possibility of developing previously discontinued agents, would benefit from a database of antibacterial compounds for scrutiny by the developers. This article describes the first free, open-access searchable database of antibacterial compounds, including discontinued agents, drugs under pre-clinical development and those in clinical trials: AntibioticDB (AntibioticDB.com). Data were obtained from publicly available sources. This article summarizes the compounds and drugs in AntibioticDB, including their drug class, mode of action, development status and propensity to select drug-resistant bacteria. AntibioticDB includes compounds currently in pre-clinical development and 834 that have been discontinued and that reached varying stages of development. These may serve as starting points for future research and development.